Transformasi Pendidikan Agama Islam Dalam Membentuk Akhlak Mahasiswa Yang Humanis Religius - Amri, Rikil Amri; Rikil Amri; TB. Ahmad Munada; Reni; Siti Zahra (Mu'allim, 2026)
This study is motivated by various events occurring in Indonesia, where education is expected to cultivate students’ humanistic and religious character, including through Islamic education. The teaching of Islamic Religious Education (IRE) is considered essential in shaping students’ humanistic-religious morals, as IRE serves as a strategic means to address social conflicts and contemporary societal issues. The objectives of this study are to describe the forms and directions of transformation in Islamic Religious Education at higher education institutions, analyze efforts to integrate humanistic-religious values into the IRE learning process, and evaluate the impact of IRE transformation on the development of students’ humanistic-religious character. This research employs a qualitative approach with a descriptive research design. This approach was selected because the study focuses on gaining in-depth understanding of the processes and meanings of IRE transformation in shaping students’ humanistic-religious character. The study emphasizes understanding values, attitudes, and behaviors developed through IRE, rather than collecting quantitative data. The findings indicate that the transformation of Islamic Religious Education at Universitas Pamulang (UNPAM) significantly contributes to shaping students’ humanistic-religious character. The transformation is implemented through curriculum renewal and more contextual, interactive teaching methods. IRE lecturers act as facilitators, fostering awareness of Islamic values within a socio-humanitarian context. Educational transformation requires adaptation to contemporary developments while remaining grounded in spiritual values. The implementation of humanistic-religious values is realized through dialogical learning, religious activities, and community service. This process cultivates empathy, tolerance, and social responsibility among students, thereby reinforcing the concept of humanistic Islamic education. Ultimately, Islamic education aims to develop individuals who are faithful, knowledgeable, and morally upright.